THE STUDY OF THE WORK CONDITIONS OF THE BORDER CROSSING POINTS OF THE ODESSA RAILWAY - Levytskyi, I. Yu. (Science and Transport Progress, 2007)
There has been executed analysis of dynamics of the car flows which cross the boundary transitions points of the Odessarailway. There also have been offered the measures directed towards the development of its transit potential.